Kesehatan sebagai Ibadah: Mengapa Menjaga Tubuh Adalah Bagian dari Keimanan - Esa Shaquille Aufa; Muhammad Nabiil Firdaus; Muhammad Alfiadi Fadilurrahman (Ikhlas : Jurnal Ilmiah Pendidikan Islam, 2024)
Health in Islam is seen as an overall part of worship and faith, where taking care of the body is a trust that must be maintained. This research aims to examine the role of health as a form of worship in Islamic teachings and highlight the importance of maintaining a healthy body as a form of devotion and faith in Allah. Using a literature review method, this research analyzes religious sources and relevant literature, and identifies a lack of attention to the relationship between physical and spiritual health in previous studies. The findings of this study show that maintaining health is not only beneficial medically but is also a spiritual obligation that is often overlooked. The results of this research emphasize that Muslims need to be more aware of the importance of physical health as part of their religious responsibilities. The implication of this research is the need to increase health education among Muslims, which emphasizes spiritual aspects as the main motivation for taking care of the body.